Semiotics Analysis of Semar Mesem Spell Performed by The Coastal Community of Jember, East Java, Indonesia - Roni Subhan; Haris Supratno; Darni Darni (Budapest International Research and Critics University, 2021)
The purpose of this study was to describe the symbolic meaning presented in Semar Mesem spell in its socio-cultural context. This study used text analysis by applying semiotic theory of Roland Barthes and considering its context in its social life of the community to obtain a comprehensive description of its symbolic meaning. The data was collected through direct interviews to the owner of spell. It was done by listening, transcribing it in English, identifying and analyzing it to formulate the research findings. The analysis showed that the symbols presented in the mantra described the elements of wisdom and virtue in communal life.